2006
DOI: 10.1111/j.1600-0501.2005.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bone apposition around biofunctionalized sandblasted and acid‐etched titanium implant surfaces

Abstract: Microrough titanium (Ti) surfaces of dental implants have demonstrated more rapid and greater bone apposition when compared with machined Ti surfaces. However, further enhancement of osteoblastic activity and bone apposition by bio-functionalizing the implant surface with a monomolecular adsorbed layer of a co-polymer - i.e., poly(L-lysine)-graft-poly(ethylene glycol) (PLL-g-PEG) and its derivatives (PLL-g-PEG/PEG-peptide) - has never been investigated. The aim of the present study was to examine early bone ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 28 publications
4
97
4
1
Order By: Relevance
“…Additive methods typically use templates fabricated through titanium plasma-spraying, electron-beam lithography, molecular self-assembly, and sol-gel transformation techniques, among others. These methods provide more complex micro-/nano-structures, and drugs can be coated onto the surface (such as the molecular self-assembly method) 40 and sub-10 nm length scale structure can be achieved (such as electron-beam lithography). 41 Subtractive methods typically use templates fabricated through blasting, peroxidation (H 2 O 2 ) or acid oxidation, and acid etching.…”
Section: Discussionmentioning
confidence: 99%
“…Additive methods typically use templates fabricated through titanium plasma-spraying, electron-beam lithography, molecular self-assembly, and sol-gel transformation techniques, among others. These methods provide more complex micro-/nano-structures, and drugs can be coated onto the surface (such as the molecular self-assembly method) 40 and sub-10 nm length scale structure can be achieved (such as electron-beam lithography). 41 Subtractive methods typically use templates fabricated through blasting, peroxidation (H 2 O 2 ) or acid oxidation, and acid etching.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that organic coating of machined screw implant surfaces providing binding sites for integrin receptors can enhance bone implant contact and periimplant bone formation. In addition, Germanier et al [46] compared RGD peptide polymer modified implant surfaces with sandblasted and acid-etched implant surfaces placed in the maxillae of miniature pigs, and confirmed that the functionalization may promote enhanced bone apposition during the early stages of bone regeneration. Despite these highly positive results, another in vivo study found that the presence of the RGD sequence did not improve the adhesion on Ti.…”
Section: Polypeptidementioning
confidence: 98%
“…Molecular selfassembly allows for the deposition of a self-assembled monolayer onto a substrate and subsequent exposure of an active terminal group that promotes specific biological functions such as the adhesion of protein and cells [94] or bone deposition [95]. This technique sounds promising because it allows obtaining a selective adhesion to the surface.…”
Section: Self-assembly Of Monolayers (Sams)mentioning
confidence: 99%